Greenland, icebergs at Kejser Franz Joseph Fjord and entrance to Kjerulf Fjord - Boyd, Louise Arner, 1887-1972 (1931)
July 29, 1931. Kaiser Franz Josef Fjord [Kejser Franz Joseph Fjord]. Entrance to Kjerulfs [Kjerulf] Fjord. On left; S.E. point. On right; Riddarborgen (Peak)- S.W. point. Photo taken looking S.W. from SS Veslekari. This is No. 2 in pan B.